Fever Goraczka - Grabowska, Barbara; Holland, Agnieszka, 1948- (New York : ITI ; Sarasota, Fla. : Distributed by Polart, 1989)
Starring Barbara Grabowska.
In Polish with English subtitles.
Videorecording of film produced in 1981.
Keywords: Revolutionaries -- Poland -- Drama; Poland -- History -- Revolution, 1905-1907 -- Drama